Experimental investigation of isothermal vapor-liquid equilibrium and estimation of excess thermodynamic properties (h(E)) of CHO2K-H2O from 278.15 to 423.15 K - Takalkar, Gorakshnath D.; Bhosale, Rahul R.; Mali, Nilesh A.; Bhagwat, Sunil S. (Journal of Chemical and Engineering Data, 2019)
In this paper, vapor liquid equilibrium (VLE) of a binary mixture, potassium formate-water (CHO2K-H2O), was measured experimentally using a dynamic moving type VLE setup in the temperature range of 313.15 to 393.15 K. Overall, large vapor pressure data points generated for the mole fraction of CHO2K from 0.023 to 0.461 and the solution temperature up to 423.15 K were used to correlate the local composition-based activity coefficient model (NRTL model). The data obtained via the thermodynamic model fitting shows good agreement with the experimental VLE data with overall average relative deviation of 2.15% and root-mean-square deviation of 0.25%. The obtained results further indicate that the binary mixture exhibits a negative deviation from the Raoult's law, which is an important characteristic of the working fluid used for a heat-activated vapor absorption system (VAS). Therefore, the CHO2K-H2O mixture can be considered as an alternative working pair that will overcome the limitations allied to the crystallization and corrosion of the commercial working fluids mainly lithium bromide-water (LiBr-H2O). The fitted nonrandom two-liquid model was further utilized to determine the excess thermodynamic properties, solution enthalpy, solution entropy, and equilibrium P-T-x (Duhring) plot.

Energetic and exergetic performance of NH3-H2O-based absorption refrigeration cycle: effect of operating factor - Takalkar, Gorakshnath Dadabhau; Bhosale, Rahul R.; Mali, Nilesh A.; Bhagwat, Sunil S. (International Journal of Exergy, 2020)
One of the major objectives while designing the vapour absorption refrigeration system (VARS) is to acquire better performance within the accessible heat source and sink temperature limit. In this paper, attempts are made to identify the temperature limit for the optimisation of a single stage ammonia refrigeration system (AAR) by performing a thermodynamic analysis. To estimate the potential of utilisation of low-grade heat energy, operating factor (R) is considered towards optimising the energetic (COP) and exergetic COP (ECOP). The simulated COP and ECOP results are expended to predict the feasibility and optimum operating region for an AAR cycle in terms of theRand various operating temperatures such asT(gen),T-abs,T-cond,T-e. The operating factorRcovers a wide range of applications i.e., from deep-freezing (253.15 K) to air conditioning (283.15 K) and from water-cooling (303.15 K) to air cooling (318.15 K).
Keywords: AAR; ammonia absorption refrigeration; cold storage; exergy; operating factor; solar energy